2019
DOI: 10.1039/c9nj03328a
|View full text |Cite
|
Sign up to set email alerts
|

Photonic band gap effect and dye-encapsulated cucurbituril-triggered enhanced fluorescence using monolithic colloidal photonic crystals

Abstract: Enhanced fluorescence was achieved by tuning the photonic band gaps in colloidal photonic crystals and host–guest chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Plasmonic enhanced fluorescence (PEF) is produced through effective coupling of a metal nanostructure localized surface plasmon resonance (LSPR) with photoexcited fluorophores to increase their photoluminescence signal intensity. PEF can be applied to improve the performance of fluorescence-based measurements in the fields of chemistry, 1 , 2 biology, 3 , 4 materials, 5 , 6 photonics, 1 , 7 and medicine. 8 , 9 Metal nanoparticles are particularly useful for PEF applications, as their LSPRs 7 , 10 , 11 can be adjusted by their geometry 7 , 10 , 11 in addition to the application of an external electric field, in combination with semiconductor materials, as reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic enhanced fluorescence (PEF) is produced through effective coupling of a metal nanostructure localized surface plasmon resonance (LSPR) with photoexcited fluorophores to increase their photoluminescence signal intensity. PEF can be applied to improve the performance of fluorescence-based measurements in the fields of chemistry, 1 , 2 biology, 3 , 4 materials, 5 , 6 photonics, 1 , 7 and medicine. 8 , 9 Metal nanoparticles are particularly useful for PEF applications, as their LSPRs 7 , 10 , 11 can be adjusted by their geometry 7 , 10 , 11 in addition to the application of an external electric field, in combination with semiconductor materials, as reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Li and co‐workers reported a 230‐fold fluorescence enhancement of rhodamine B by using diffusion‐swelling approach on the CPC [20] . Earlier, we demonstrated a host‐guest chemistry of cucurbituril supported by colloidal photonic crystals for the fluorescence enhancement of rhodamine B [21] . Chen et al .…”
Section: Introductionmentioning
confidence: 63%
“…[20] Earlier, we demonstrated a host-guest chemistry of cucurbituril supported by colloidal photonic crystals for the fluorescence enhancement of rhodamine B. [21] Chen et al reported a hydrophobic building block to construct highperformance CPCs and utilized it for the fluorescence enhancement of quantum dots by 8-fold. [22] In another study Yuan et al reported a 250-fold enhancement in the fluorescent signal of perovskite nanocrystals by using CPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pillai et al also found that the fluorescence intensity of rhodamine B increased when added to CB[7]. When the concentration of CB[7] was 1.5-fold greater than that of rhodamine B, fluorescence intensity was found to increase 6.7-fold . It should be noted that the encapsulation of CB[8] causes a stronger fluorescence enhancement than CB[7], principally because the larger inner void in CB[8] allows the encapsulation of two fluorescent molecules that form a dimer inside, the formation of which affects intramolecular motion …”
Section: Applications Of Cb Homologuesmentioning
confidence: 97%
“…When the concentration of CB [7] was 1.5-fold greater than that of rhodamine B, fluorescence intensity was found to increase 6.7-fold. 96 It should be noted that the encapsulation of CB [8] causes a stronger fluorescence enhancement than CB [7], principally because the larger inner void in CB [8] allows the encapsulation of two fluorescent molecules that form a dimer inside, the formation of which affects intramolecular motion. 97 Due to the advantages of CB encapsulation of fluorescent dyes, their simple and rapid encapsulation by CB, and the extremely stable complexes formed, a new type of CB-based fluorescent probe has been developed.…”
Section: Applications Of Cb Homologuesmentioning
confidence: 99%